Management of Bakanae disease of rice - Hossain, KS; Mia, MAT; Bashar, MA (Bangladesh Journal of Botany, 2018)
Bakanae disease is widely distributed in all rice growing areas of the world. In Bangladesh, it is one of the major diseases of rice. Four methods were tested for management of this disease, of which, roguing proved ineffective in a field investigation. Among the 15 fungicides tested in vitro, all of them were found effective in various degrees against the pathogen of the disease. Best effective 4 were selected for seed treatment and know (50% carbendazim WP) was the most effective followed by folicur (25% Tebuconazole EC), protaf (25% Propiconazole EC) and celest extra (2.5% Fludioxonil and 2.5% Difenoconazole EC). In the field, foliar spray of folicur, knowin and protaf was found ineffective to control bakanae disease. Looking for resistant one, 46 BRRI released varieties, “Purbachi”- a Chinese variety and 40 landraces of BRRI germplasm were tested in vitro against the pathogen. All these varieties and landraces were susceptible to the test pathogen in various degrees. Among the released varieties lower susceptibility were found in BR 23 and BR 11. Whereas, among the varieties and landraces the lowest was found in A23. Therefore, A23 may be suitable for use in the development of varieties resistant to bakanae rice disease.